A COMPARATIVE STUDY OF COGNITIVE PROCESSING IN ORAL MATHEMATICS TESTS AMONG MALAYSIAN ORANG ASLI PUPILS - Arsaythamby Veloo; S. Kanageswari Suppiah Shanmugam; Suheysen Revindran (Malaysian Journal of Learning and Instruction, 2025)
Purpose – This study investigates the mathematics performance of Orang Asli pupils across two cognitive domains—Knowing and Applying—using three oral mathematics tests developed in different languages: the academic language (Bahasa Melayu) (OBM), the academic native language (Bahasa Semai) (OSL), and the tribal native language (Bahasa Temiar) (OTL).